2005
DOI: 10.1007/s10038-005-0229-9
|View full text |Cite
|
Sign up to set email alerts
|

Paternal uniparental disomy of chromosome 14 and unique exchange of chromosome 7 in cases of spontaneous abortion

Abstract: To investigate the involvement of uniparental disomies (UPDs) in spontaneous abortion, the polymorphic patterns of microsatellites on each chromosome were analyzed in 164 cases of abortion. Eighty-three of the 164 cases had chromosomal abnormalities. In 79 of the remaining 81 cases with normal karyotypes, the microsatellite analysis revealed that biparental patterns were present in the informative microsatellites in all chromosomes. In one of the remaining two cases, however, the polymorphic patterns of chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
8
0
8
Order By: Relevance
“…However, UPD also causes abnormal embryonic/fetal development or even miscarriage, although the frequency of UPD-associated miscarriage may be low, which was estimated to occur in < 3% of miscarriage cases. 21,22 Several studies found that UPDs, for example, with maternal uniparentalheterodisomy of chromosome 9, 21 paternal UPD of chromosome 14, 22 maternal uniparentalisodisomy and uniparentalheterodisomy of chromosome 16, 23 and paternal uniparentalisodisomy of chromosome 21, 21 could cause miscarriage. Moreover, it was well known that wholegenome UPD was not compatible with life, and paternal origin would lead to complete hydatidiform mole, resulting in embryonic death.…”
Section: Discussionmentioning
confidence: 98%
“…However, UPD also causes abnormal embryonic/fetal development or even miscarriage, although the frequency of UPD-associated miscarriage may be low, which was estimated to occur in < 3% of miscarriage cases. 21,22 Several studies found that UPDs, for example, with maternal uniparentalheterodisomy of chromosome 9, 21 paternal UPD of chromosome 14, 22 maternal uniparentalisodisomy and uniparentalheterodisomy of chromosome 16, 23 and paternal uniparentalisodisomy of chromosome 21, 21 could cause miscarriage. Moreover, it was well known that wholegenome UPD was not compatible with life, and paternal origin would lead to complete hydatidiform mole, resulting in embryonic death.…”
Section: Discussionmentioning
confidence: 98%
“…The unavailability of parental DNA questions the results, but both parents were noted as being healthy and the identical mutation event in maternal and paternal meiosis seems highly unlikely. In a study on the relevance of UPD for spontaneous abortions Tsukishiro et al found telomeric maternal isodisomy 7q 106. Genes on 7q are considered to be relevant for autism spectrum disorder; so in a study on 60 pedigrees each with at least one individual affected by autism spectrum disorder, one case of not exactly defined interstitial maternal UPD 7q was identified 108.…”
Section: Segmental Upd Associated With a Normal Karyotypementioning
confidence: 99%
“…Accumulating evidence is supporting the view that a distinct phenotype is also associated with paternal UPD 14 (pat UPD14). Currently, 13 cases of pat UPD for the entire chromosome 14 and one case of segmental pat UPD 14 have been reported (Table 1) Furthermore, pat UPD14 has recently been found in a human spontaneous abortion (Tsukishiro et al, 2005). Clinical features described in almost all cases include polyhydramnios, small thorax with abnormally curved ribs, dysmorphic facial features and severe postnatal respiratory distress.…”
Section: Introductionmentioning
confidence: 99%